Echocardiographic Evaluation of Patent Ductus Arteriosus in Preterm Infants - Arlettaz, Romaine (Frontiers in Pediatrics, 2017)
Patent ductus arteriosus (PDA) is part of the typical morbidity profile of the preterm infant, with a high incidence of 80–90% in extremely low birth weight infants born before 26 weeks of gestation. Whereas spontaneous closure of the ductus arteriosus (DA) is likely in term infants, it is less so in preterm ones. PDA is associated with increased mortality and various comorbidities including cardiac failure, need for respiratory support, bronchopulmonary dysplasia, pulmonary or intracranial hemorrhage, and necrotizing enterocolitis; however, there is no proven causality between these morbidities and the presence of DA. Thus, the indication to close PDA remains highly controversial. This paper focuses on echocardiographic evaluation of PDA in the preterm infant and particularly on the echocardiographic signs of hemodynamic significance.